Imran Khan protests (Pakistan) - Voidly (2022)
CRITICAL severity censorship detected in Pakistan. Confidence: 90%. Data sourced from OONI.
Censorship Incident ID: PK-2022-0001
Keywords: censorship; PK; censorship; critical